Liposome fusogenic enzyme-free circuit enables high-fidelity determination of single exosomal RNA. (April 2023) - Sun, Zixin; Chen, Xiaohui; Niu, Ruyan; Chen, Hengyi; Zhu, Ying; Zhang, Chong; Wang, Liu; Mou, Huaming; Zhang, Hong; Luo, Yang
Abstract: Accurate determination of single exosomal inclusions in situ presents a significant challenge due to their extremely low abundance as well sub-100 nm vesicle dimensions. Here, we created a Li posome F usogenic E nzyme-free circuit (LIFE) approach for the high-fidelity identification of exosome-encapsulated cargoes without destroying the vesicle integrity. The probe-loaded cationic fusogenic liposome could capture and fuse with a single target exosome, enabling probes delivery and target biomolecule-initiated cascaded signal amplification in situ . Then the DNAzyme probe encountered conformal change upon exosomal microRNA activation, and generated a convex DNAzyme structure to cleave the RNA site of substrate probe. After that, the target microRNA could be released to introduce a cleavage cycle to yield amplified fluorescence readout. Therefore, trace cargoes in a single exosome could be accurately determined by elaborately controlling the ratio of introduced LIFE probe, paving the way toward the exploration of a universal sensing platform for the assessment of exosomal cargoes to facilitate early disease diagnosis and personalized treatment. Graphical abstract: Image 1 Highlights: This approach proposed a single-exosome detection strategy enabling high-fidelity identification of exosome-encapsulated trace cargoes in situ. A detection limit of 46.5 ​fM in the LIFE approach is achieved for 2 ​h. The LIFE approach has a better detection capability for distinguishing exosomal-miR-122 between tumor patients and healthy individuals, as evidenced by comparing with the RT-qPCR ​approach.